The Orthodoxy of Special Education Among Public, Private, and Islamic Secondary Schools Providing Inclusive Education - Suprihatiningrum, Jamil; Palmer, Carolyn; Aldous, Carol (Jurnal Pendidikan Agama Islam, 2022)
Purpose – The extent to which a special education orthodoxy influences teachers’ understanding and practicing of the idea of inclusion in teaching and learning is essential to be revealed to construct the meaning of inclusion for the Indonesian context. Design/methods/approach – Thirteen participants of three types of Schools Providing Inclusive Education (SPIE) i.e., Sekolah Harapan (public), Sekolah Mulia (Islamic), and Sekolah Wijaya (private) in the Special Province of Daerah Istimewa Yogyakarta were selected purposively, and a qualitative case study was conducted using an in-depth interview to gather the data. Data analysis is carried out inductively and deductively to obtain more in-depth results. Findings – All participants articulated inclusive education is a placement for students with special education needs and disabilities (SEND) in the general education system. All students with SEND were welcomed in Sekolah Harapan but were then labeled and pulled out to a resource room to be educated separately by a support teacher. In Sekolah Mulia, most students were visually impaired without support teacher provided to assist them. Teaching and learning were very minimal offered various strategies, media, and assessments; mirrored the special education model. Sekolah Wijaya, in contrast, implemented a more inclusive education model, no labeled was marked for students with SEND and promoted an inclusive climate through learning activities. Research limitation – The small number of participants meant that the findings cannot be generalized as the participants cannot be considered representatives of secondary schools in Yogyakarta or Indonesia. Originality/value – Teachers in three SPIE investigated are willing to promote inclusive education although the orthodoxy of special education philosophy still has been flavoring most of the teachers’ language in defining and practicing the inclusive concept.